Giant Hepatic Hemangioma: A Case Report (Journal of Rangpur Medical College, 2026)
Hepatic hemangiomas are the most common benign liver tumors, typically asymptomatic and discovered incidentally. Giant hepatic hemangiomas (>10 cm) are rare and may present with symptoms due to mass effect. This report describes a 45-year-old woman presenting with abdominal fullness due to a massive hepatic hemangioma measuring approximately 20.5×17.5×23 cm in the left lobe, with a smaller lesion in the right lobe. Diagnosis was confirmed via ultrasonography, contrast-enhanced computed tomography (CECT), and fine-needle aspiration cytology (FNAC). Laboratory findings included mild normocytic normochromic anemia and leucopenia, with normal liver function tests and tumor markers. Management was conservative, with recommendations for open biopsy. This case underscores the diagnostic utility of multiphasic imaging and the benign nature of these lesions, supported by a review of similar cases in the literature.J Rang Med Col.2026 Mar;11(1):221-225